Comparative study on the performance of butt fusion-welding processes for nuclear safety class large-diameter thick-walled PE pipes - Wang, Zhenchao; Wang, Bin; Xiang, Aimin; Jiao, Di; Yu, Fa; Zhang, Qiuju; Zhao, Xiaoying (Nuclear engineering and technology, 2024)
New technologies in polymer synthesis and pipe extrusion equipment have led to the commercialization of high-performance, large-diameter, thick-wall high density polyethylene (HDPE) pipes. They have been used in the field of seawater transport and cooling to replace metal pipes, due to their advantages of high corrosion resistance and extensibility. Connection of HDPE pipe is important as it determines the safety of the entire piping system. Butt fusion welding is commonly used for HDPE pipe connection but may cause the formation of weak points in the welded joints, interfering the reliability of the pipeline system in the application of nuclear power plants. At present, there is a lack of research on evaluating the performance of welded joint for large-diameter thick-wall HDPE pipes made by butt fusion-welding. The purpose of this study is to investigate the influence of three different butt fusion-welding processes, i.e., single low pressure (SLP), single high pressure (SHP) and dual low pressure (DLP), by evaluating the performance of their welded joints, including characterizing tensile strength, extensibility, crystallinity and hardness. In specific, a thick-wall HDPE pipe with OD of 812.8 mm and wall thickness of 74 mm which is certified for nuclear safety class was used for study. Representative specimen from the outer, middle and inner part across the wall of the main pipe body and welded joints were taken for testing. Different test methods and specimens were designed to assess the feasibility of evaluating the welding performance from different welding process. The results showed that the mechanical properties of different locations of the welded joints were different, and the tensile strength and fracture energy of the middle part of the joint were lower than that of the inner and outer parts, which could be caused by the difference in the crystallinity and thickness of the melting zone influenced by welding processes, as can be seen from the analysis of DSC test and morphology observation. Hardness testing was conducted on the section of the welded joints, and it revealed that the micromechanical properties of the welded joints in the region of the heat-affected zone were enhanced significantly, which may be due to the annealing effect caused by welding process. In summary, The DLP process resulted in the best extensibility of the welded joints among three processes, suggesting that the joining pressure from welding process plays an important role in affecting the extensibility of the welded joints.